2022
DOI: 10.1186/s13287-022-03107-4
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity reduction and mitochondrial and lysosomal dysfunction of mesenchymal stem cells aging in vitro

Abstract: Background Mesenchymal stem cells (MSCs) have been extensively used for the treatment of various diseases in preclinical and clinical trials. In vitro propagation is needed to attain enough cells for clinical use. However, cell aging and viability reduction caused by long-time culture have not been thoroughly investigated, especially for the function of mitochondria and lysosomes. Therefore, this study was designed to detect mitochondrial and lysosomal activity, morphological and functional cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Therefore, these studies indicate that the mitochondrial dysfunction in obesity is associated with inflammation, insulin resistance, and hyperglycemia. Regarding the relationship of cell activity and mitochondrial function, our previous study shows that mesenchymal stem cells (MSCs) after long-time culture in vitro exhibit senescence phenotype, reduced biological activity and impaired mitochondrial morphological and function [ 18 ]. In hematopoietic stem cells (HSCs), the integrity of mitochondrial respiratory chain is essential for HSC differentiation and maintenance of adult HSC quiescence [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these studies indicate that the mitochondrial dysfunction in obesity is associated with inflammation, insulin resistance, and hyperglycemia. Regarding the relationship of cell activity and mitochondrial function, our previous study shows that mesenchymal stem cells (MSCs) after long-time culture in vitro exhibit senescence phenotype, reduced biological activity and impaired mitochondrial morphological and function [ 18 ]. In hematopoietic stem cells (HSCs), the integrity of mitochondrial respiratory chain is essential for HSC differentiation and maintenance of adult HSC quiescence [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In quiescent neural stem cells, impaired lysosome function causes more accumulation of protein aggregates and decreases the activation of quiescent neural stem cells [ 26 ]. Our previous study found that MSCs after long-time culture exhibit reduced autophagy and lysosomal dysfunction [ 18 ]. In hematopoietic stem cells, lysosomes are asymmetrically distributed in daughter cells, affecting the fate of recipient cells [ 29 ].…”
Section: Introductionmentioning
confidence: 99%